The HLA DPB1*02:01:02 and DQB1*05:02:01 alleles as possible risk factors for colorectal carcinoma in the Malaysian population - Nor Adzimah Johdi; Sri Noraima Othman; Zuraini Abd Razak; Luqman Mazlan; Ismail Sagap; Rahman Jamal (Pusat Perubatan Universiti Kebangsaan Malaysia, 2016)
Many studies have shown that the immune response highly depends on the inheritance of specific HLA genes in promoting the generation of T cells for the elimination of pathogens. Loss or alteration of HLA antigen expression in tumor cells has been observed in a variety of human malignancies leading to immune escape or immune resistance. We investigated whether the inheritance of certain alleles of HLA class II genes confers susceptibility or resistance towards the development of colorectal carcinoma (CRC). Molecular typing of HLA DRB1, DQB1 and DPB1 alleles in 42 patients diagnosed with CRC and 50 ethnically matched healthy controls using the PCR-sequence based typing (PCR-SBT) was conducted. The HLA DPB1*02:01:02 was significantly higher in CRC patients (38.1%, p=0.0189) compared to healthy controls (16%). Also, HLA DQB1*05:02:01 was present in 28.6% of CRC patients but only 10% of healthy controls (p=0.0278). The odds ratios for HLA DPB1*02:01:02 and HLA DQB1*05:02:01were 3.23 and 3.60, respectively. There were no significant association observed for the DRB1 allele with CRC. Our study suggests that the HLA DPB1*02:01:02 and HLA DQB1*05:02:01 alleles may confer a higher risk for CRC.